I. Concentrate: Roughage ratios in pelleted rations for fattening lambs. II. 3-mg. Stilbestrol implants for lambs fed pelleted rations. - Menzies, C.S.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
A summary of three years' study of the relationship of physical balance to the utilization of pelleted and nonpelleted fattening lamb rations was reported in Circular 358. Results of this work indicated the following: (l) the optimum ratio in nonpelleted lamb-fattening rations was 45 percent. concentrate to 55 percent roughage; (2) pelleted rations produced faster, more efficient ga.ins than nonpelleted rations' (3) pelleted rations consisting of 40 percent concentrate and 60 percent roughage produced gains as fast and as efficiently as pelleted rations of 50 percent concentrate and 50 percent roughage; and (4) field-cured alfalfa hay produced faster and more economical gains than dehydrated alfalfa when mixed and pelleted with a concentrate. This year's test was concerned primarily with finding the optimum concentrate to roughage ratio for pelleted lamb fattening rations and with determining the value of feeding loose hay with a complete pelleted ration for lambs. The value of 3-mg. stilbestrol implants also was studied.
Keywords: Sheep; Roughage; Rations; Implants